2020
DOI: 10.3390/ijms21124202
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired Expression of Chloroplast HSP90C Chaperone Activates Plant Defense Responses with a Possible Link to a Disease-Symptom-Like Phenotype

Abstract: RNA-seq analysis of a transgenic tobacco plant, i-hpHSP90C, in which chloroplast HSP90C genes can be silenced in an artificially inducible manner resulting in the development of chlorosis, revealed the up- and downregulation of 2746 and 3490 genes, respectively. Gene ontology analysis of these differentially expressed genes indicated the upregulation of ROS-responsive genes; the activation of the innate immunity and cell death pathways; and the downregulation of genes involved in photosynthesis, plastid organi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 77 publications
(92 reference statements)
1
22
0
Order By: Relevance
“…Previously, we described the transcriptome changes preceding the chlorosis developments and relevant biological events in another chlorosis model, i-hpHSP90C transgenic plant system [ 20 ], which is similar to the present i-amiCHLI plants but differs in the silencing target. To find out the common features in the chlorosis development in these two transgenic systems, we compared the results from GO enrichment analyses with up- and down-regulated genes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we described the transcriptome changes preceding the chlorosis developments and relevant biological events in another chlorosis model, i-hpHSP90C transgenic plant system [ 20 ], which is similar to the present i-amiCHLI plants but differs in the silencing target. To find out the common features in the chlorosis development in these two transgenic systems, we compared the results from GO enrichment analyses with up- and down-regulated genes.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously generated two inducible silencing systems for CHLI and HSP90C in tobacco and found that the silencing of these genes could stimulate the plants to develop chlorosis [ 18 , 19 , 20 ]. As discussed previously [ 20 ], these systems have advantages over the experimental systems with the virus- or viroid-infected plants because, in these transgenic lines, it is possible to analyze those plant cells that have committed to developing but not exhibited chlorosis. Utilizing the advantages of these systems, in our previous and current studies, an RNA-seq method was implemented to explore the early molecular changes, which lead to chlorosis development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations